Księgozbiór specjalistyczny Henryka Grohmana (1862– 1939) a jego kolekcja grafiki nowoczesnej - Dragońska, Urszula (Artium Quaestiones, 2023)
This article is the first study of the library belonging to the Łódź industrialist and art collector Henryk Grohman (1862–1939). It attempts to answer the question of the degree to which analysing these volumes, which are now housed in the collections of the University of Warsaw Library and the National Museum in Warsaw, can prove helpful in the study of art collections. The methodology for researching historical book collections was used to reconstruct and describe the library. These inquiries resulted in more than 165 titles being determined, which originally belonging to Grohman and covered oriental and European arts and crafts, as well as graphic and drawing arts (about 60). These included monographs, albums, and critical catalogues, exhibition and antiquarian nature, published mainly in Western Europe before 1914. The collector’s specialized book collection, built up on an ongoing basis, overlapped with his artistic interests and had the character of a utilitarian library. From the point of view of the study of graphic collections of the late 19th and early 20th centuries, the reference libraries of their creators seem to be of particular importance. In times when taste no longer sufficed to create a valuable collection, and quality and rarity became the main criteria for selecting graphic works, specialized literature on the subject was of help. Created by art historians, collection curators, art market experts, and also private collectors, it introduced the nuanced world of graphic arts. It provided a tool to help identify a print, determine its state, edition and quality, and thus determine the value of a given work. The preserved publications from Grohman’s library were therefore regarded as sources of specialized knowledge that the collector could not acquire either during his education or in his native environment. Three publications have been analysed in detail in the context of Grohman’s graphic arts collection: the series Le peintre-graveur illustré by Loys Delteil (1906–1926), the two-volume catalogue of Jean-Louis Forain’s lithographs and etchings by Marcel Guérin (1910, 1912), and the album devoted to the engravings of Fank Bangwyn prepared by Frank Newbolt (1908). These are publications reflecting the thriving activity of the circle of print enthusiasts of the late 19th and early 20th centuries, which had a significant impact on the dissemination of knowledge about this field of art. The series of relationships revealed between the collection of prints and drawings and the reference library significantly expanded the knowledge on its creator and how the collection was formed. It made it possible to appreciate the collector’s expertise and artistic taste, to observe how his awareness grew, influencing decisions on subsequent purchases, and also to detail the provenance of certain works. Thanks to the research field being expanded to include Grohman’s library, the findings on his graphic collection have become more complete and reliable.